Identifying the Potential of Cultural Events as A Reinforce of Tourism Identity on Sibandang Island - Andriani, Nukeu Novia; Hadi, Aji Prasetya; Fadhila, Jihan (Jurnal Pariwisata Terapan, 2024)
Tourism destination development is a crucial program in supporting government efforts to strengthen the tourism sector. In addition to climate and scenery, which serve as primary assets, maximizing cultural and historical attributes, as well as organizing special events, is essential for destination development. Pulau Sibandang, with its unique geological structure and landscape, represents natural heritage and the geological evolution of the Toba eruption, along with its tangible and intangible cultural diversity. Strengthening the identity of the destination is key, as based on the Tourist Area Life Cycle (TALC) model, Pulau Sibandang is still in the exploration phase of tourism development. This early phase involves natural and cultural attractions that have yet to be fully maximized. Cultural event organization can be a powerful tool to attract tourists and build the destination’s reputation. This study employs the ADO-ODTWA (Analisis Operasi Objek dan Daya Tarik Wisata Alam) method to analyze the operational aspects of natural tourism attractions. The findings reveal that, while Pulau Sibandang has significant cultural and natural attractions, there are areas needing improvement, particularly accommodation and marketing. Recommendations include integrating community participation in event planning and enhancing infrastructure to better support tourism. The study identifies the potential for cultural event-based festivals and provides a prototype design for such events in Pulau Sibandang, Muara District, North Tapanuli Regency.